Cultural transmission of attitudes and behaviours from parents, peers and grandparents - Monica Tamariz; Bradley Walker; Matthew Bennett; José Segovia-Martín; Nicolas Fay (PLoS ONE, 2026)
This study investigates how attitudes and behaviours are transmitted across generations and social networks, focusing on the relative influence of parents, grandparents, and peers. Building on the influential work of Cavalli-Sforza and Feldman (1982), we aimed to disentangle vertical and horizontal pathways of cultural transmission and assess their contribution to the stability and variation of cultural traits in a contemporary population. We conducted a large-scale survey involving 1905 university students in Australia and 4000 of their parents, grandparents, and friends. Participants reported their attitudes and behaviours across domains such as religiosity, politics, environmentalism, health, and leisure. Responses were analysed using factor analysis, path modelling, correlational analysis, and simulations based on additive transmission models. Our results show that cultural resemblance is strongest for religiosity, political orientation, environmentalism, and health behaviours. These traits exhibited clear vertical transmission from parents to children, with additional indirect influence from grandparents. Peer similarity was also evident, suggesting horizontal transmission and/or peer selection. Traits such as media use, music, and reading habits showed weaker familial resemblance and appeared more influenced by non-familial or contextual factors. Simulations confirmed that cultural traits are more likely to be adopted when shared by both parents and peers, though for some traits (especially left-wing political views and non-religiosity) external influences predominated. The findings demonstrate that cultural transmission is domain-specific and shaped by both family structure and social networks. Vertical and horizontal pathways contribute jointly, but their strength varies by trait. These results underscore the importance of integrating biological, psychological, and sociocultural factors to understand the persistence and evolution of beliefs and behaviours over generations.